Now You Feel both: Galvanic Vestibular Stimulation Induces Lasting Improvements in the Rehabilitation of Chronic Tactile Extinction - Schmidt, Lena; Utz, Kathrin S.; Depper, Lena; Adams, Michaela; Schaadt, Anna-Katharina; Reinhart, Stefan; Kerkhoff, Georg (Frontiers in Human Neuroscience, 2013)
Tactile extinction is frequent, debilitating and often persistent after brain damage. Currently, there is no treatment available for this disorder. In two previous case studies we showed an influence of galvanic vestibular stimulation (GVS) on tactile extinction. Here, we evaluated in further patients the immediate and lasting effects of GVS on tactile extinction. GVS is known to induce polarity-specific changes in cerebral excitability in the vestibular cortices and adjacent cortical areas. Tactile extinction was examined with the Quality Extinction Test (QET) where subjects have to discriminate six different tactile fabrics in bilateral, double simultaneous stimulations (DSS) on their dorsum of hands with identical or different tactile fabrics. Twelve patients with stable left-sided tactile extinction after unilateral right-hemisphere lesions were divided into two groups. The GVS group (N=6) performed the QET under six different experimental conditions (two Baselines, Sham-GVS, left-cathodal/right-anodal GVS, right-cathodal/left-anodal GVS, and a follow-up test). The second group of patients with left-sided extinction (N=6) performed the QET six times repetitively, but without receiving GVS (control group). Both right-cathodal/left-anodal as well as left-cathodal/right-anodal GVS (mean: 0.67 mA) improved tactile identification of identical and different stimuli in the experimental group. These results show a generic effect of GVS on tactile extinction, but not in a polarity-specific way. These observed effects persisted at Follow-up. Sham-GVS had no significant effect on extinction. In the control group, no significant improvements were seen in the QET after the six measurements of the QET, thus ruling out test repetition effects. In conclusion, GVS improved bodily awareness permanently for the contralesional body side in patients with tactile extinction and thus offers a novel treatment option for these patients.